Belarus – Japan: new opportunities under new regional conditions - Esin, Ruslan O. (Journal of the Belarusian State University. International Relations, 2018)
This article is dedicated to the analyses of the development of the Belarus – Japan relations, traditionally friendly and constructive nature of the interaction is emphasized. The purpose of this article is to assess the effectiveness of bilateral relations, drawing attention to the large potential of cooperation. It is concluded that there is a need to intensify the political dialogue between the two countries, deepen the Belarusian-Japanese relations in the trade, economic and humanitarian spheres, as well as to strengthen international partnership.
Keywords: Belarusian-Japanese relations; Belarusian foreign policy; humanitarian and economic cooperation; intensi fication of political dialogue